A laryngeal inflammatory polyp in a miniature dachshund. Issue 3 (15th May 2020) - Sugimoto, Keisuke; Kanda, Teppei; Mitsui, Ikki; Miyabe, Masahiro; Maeta, Noritaka
Abstract: A 15‐year old, female miniature dachshund was presented for a 5‐year history of progressive dyspnoea. A laryngeal mass was detected on cervical radiographs. Surgery was performed 5 days later to reduce the volume of the mass and to obtain biopsy samples; the dyspnoea improved. Based on the histopathological findings, the mass was diagnosed as inflammatory polyp. This case of inflammatory polyp in the larynx suggests that it should be listed in the differential diagnoses for laryngeal masses in dogs and that surgical treatment may be curative. Abstract : A laryngeal inflammatory polyp in a miniature dachshund was diagnosed and the treatment was successful.